PENERAPAN METODE KASUS TERHADAP HASIL BELAJAR PADA MATERI KSP - Rahayu, Krida Puji (FKIP Unirow Tuban, 2020)
This research aims to determine the effectiveness of the application of the case method by using audio-visual media to the learning outcomes. The population in this study is a grade XI SCIENCE student. Sampling is done randomly using the random sampling cluster technique. Based on the average estimated test results were obtained the average results of the experiment Group learning and the control group. The results of the submission are learned to get the percentage of classical learning submission for the experimental group of 98% and the control group at 76%. The results of observation of the affective and psychomotor domains were obtained the average value of students in the experimental group ≥ 65.